Gadamer: Between Heidegger and Habermas - Scheibler, Ingrid H. (Rowman & Littlefield Publishers, 2000)
One of the first book-length studies to examine Gadamer's relation to Heidegger in depth, this important work looks at the ways in which Gadamer positively appropriates central elements of Heidegger's work as well as the way he extends Heidegger's critique of Western metaphysics, avoiding and tacitly challenging some of the most problematical aspects of Heidegger's work. By examining two of the central concepts in Gadamer's work, tradition and language, and by analyzing Gadamer's relation to his mentor, Martin Heidegger, Sheibler successfully shows that far from being the conservative both modernist and post-modernist critics have accused him of being, Gadamer anticipates a number of concerns central to post-modern or post-structuralist thought.